Awareness level among government employees in property investment: a study in department of veterinary services Selangor / Khairunnisa Nazri - Nazri, Khairunnisa (2019)
Property market has been the major investment in Malaysia economy in recent years proved by Malaysian Investment Development Authority (2018) that recorded Selangor as top contributor on 23% country profit includes property investment practice but ratio of investors were led by private sector for 32% over public sectors. As government employees benefits advanced from private sector, they should major property investment instead of private sectors. Thus, this study aim to identify understanding and awareness level among government employees in property investment .based on demographic factor and analyzed factors that considered before start invest in property. Research data obtained through questionnaire and surveys responded by 60 employees from Department of Veterinary Services Selangor. Results obtained work as useful information for government and other parties to frame wise planning particularly in property investment. Education proved to impact level of awareness could assist government to improve property investment practice. Furthermore, three elements considered before invest is financial performance, property characteristics and risk management. All related parties should play role promote property investment in Malaysia to create better property market in country and improve their life position.